Redescription and molecular characterisation of Dujardinascaris madagascariensis and a note on D. dujardini (Nematoda: Heterocheilidae), parasites of Crocodylus niloticus, with a key to Dujardinascaris spp. in crocodilians - Mašová, Šárka; Baruš, Vlastimil; Seifertová, Mária; Malala, John; Jirků, Miloslav (Zootaxa, 2014)
An examination of one specimen of Nile crocodile, Crocodylus niloticus (Laurenti, 1768), from Lake Turkana (Kenya), revealed the presence of two ascaridoid nematodes belonging to the genus Dujardinascaris Baylis, 1947. Dujardinascaris madagascariensis Chabaud & Caballero, 1966 was studied by scanning electron microscopy, redescribed, and differentiated from D. dujardini (Travassos, 1920). Dujardinascaris madagascariencsis is the second of the genus to be sequenced. An internal fragment of the small ribosomal subunit and nuclear ribosomal DNA internal transcribed spacer 2 region were amplified—the slowly evolving 18S gene region was used for phylogenetic analysis. Molecular data confirmed affinity of D. madagascariensis to the family  Heterocheilidae and revealed its closest relationship with D. waltoni. A key to the species of Dujardinascaris parasitizing crocodiles is provided.